Social utopia as a future scenario in the Modern - Клешня, Г. М. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The author provides a philosophical reception of social utopia as a script of future in the Modern era. It is shown that social utopiashave become an important component of social, economic, political and cultural development of society and the basis of social progress at a certain stage of human development.